Influência da participação de mulheres nos órgãos de governança sobre o desempenho das cooperativas de crédito no Brasil - Klochinski, Cleiton Luiz (2023)
This study investigated the presence of women in the management of single credit unions in Brazil and their impact on the performance of these organizations. To achieve this objective, performance indicators such as Return on Assets (ROA) and Return on Equity (ROE) and female participation on boards of directors, supervisory boards, executive board and as president of cooperatives were analyzed, with the sample consisting of 597 cooperatives in 2021 and 598 in 2022. Using a descriptive, documental, and quantitative approach, with the use of Pearson's correlation techniques and multiple linear regression, data analysis tests were conducted. In the equational models used, the variables ROA and ROE were defined as dependent, and those that characterized female participation in governance bodies as independent, and characteristics of the cooperative in financial and governance terms were considered as control variables in the estimations. As for female participation, it was observed that women occupied, on average, around 15.5% of the seats on the boards of directors, 23.0% on the supervisory boards and 21.4% on the executive board. The presence of women as CEOs was recorded in approximately 20.2% of the studied cooperatives. Statistical analysis revealed significant correlations between female participation in boards of directors and supervisory boards and performance indicators. The correlations related to female participation with performance were negative, suggesting that the increase in female representation in these bodies is associated with a decrease in ROA and ROE indicators. Female participation in the executive board and as CEO did not show statistical significance. Robustness tests confirmed these associations. The conclusions of this study can contribute to the practices of credit unions and other organizations that seek to promote diversity in their governance bodies. In addition, they contribute to the theoretical debate about the role of women in governance and how this affects organizational performance. The conclusions reported above alert to the importance of ensuring that women's participation is effective and not just symbolic, avoiding tokenism. It is important to recognize the limitations of this study. The decentralized availability of information and the difficulty in accessing specific data from cooperatives were challenges faced. In addition, the lack of meeting minutes limited the understanding of women's effective contributions to decisions, and these aspects are possibilities for future investigations.